Institutional context of soil information in Burkina Faso - Kalčić, Špela (2015)
This study examines the institutional context of soil information in Burkina Faso. Data was collected using informant interviews conducted over a 1-month period in Burkina Faso between May and June 2015. Interviewees were drawn from the consultant’s Internet survey and recommendations from the representatives of interviewed entities (a snowball method). Given the objectives of the study, the interviews were conducted with representatives of 11 entities in Ouagadougou, Kamboinse and Bobo-Dioulasso. Interviewees spanned the spectrum of those concerned with soil fertility management issues including researchers, university lecturers and government officials. A semi-structured interview questionnaire prepared according to Terms of Reference for a Consultant guided the discussion between the interviewer and respondent to explore specific topics in an open, conversational manner. The questions concerned integration of soils into agricultural planning and implementation, perceived constraints of improving access to fertilizers and other soil management options, the level of technical knowledge in key training institutes for extension personnel and incorporation of farmer soil management strategies into curriculums of national training institutes. Specific information on civil society sector, policy and strategy documents on soil fertility management, access to fertilizers and the agribusiness private sector was complemented through an additional Internet and professional literature survey.